2020
DOI: 10.3390/ijerph17145255
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Self-Assessment of Caring Behaviors in Nurse–Patient Interactions: A Cross-Sectional Study

Abstract: Nurse–patient interactions based on caring behaviors ensure better working conditions and better-quality healthcare. The aim of this quantitative study is to examine how nurses self-assess the frequency of applying caring behaviors in nurse–patient interactions and to identify the differences in the application frequency of caring behaviors in relation to work experience and education level. The respondents were Bachelor of Science (BSc) nurses and nurses with basic training (VET) employed in different clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 49 publications
0
33
1
2
Order By: Relevance
“…4 Another studies showed that nurses are more focused on the application of skills or carrying out a task than on existing caring behaviors that demonstrate compassion, love, kindness, and relationships. 5 Their work performance appearance is influenced by job satisfaction. [6][7][8] Nurses believe that the quality of care provided by their work unit has a strong impact on job satisfaction, and believe that their work unit provides excellent quality of care that also provides the highest level of satisfaction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Another studies showed that nurses are more focused on the application of skills or carrying out a task than on existing caring behaviors that demonstrate compassion, love, kindness, and relationships. 5 Their work performance appearance is influenced by job satisfaction. [6][7][8] Nurses believe that the quality of care provided by their work unit has a strong impact on job satisfaction, and believe that their work unit provides excellent quality of care that also provides the highest level of satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Another studies showed that nurses are more focused on the application of skills or carrying out a task than on existing caring behaviors that demonstrate compassion, love, kindness, and relationships. 5 Their work performance appearance is influenced by job satisfaction. 6-8 …”
Section: Introductionmentioning
confidence: 99%
“…The PH sample showed a lower level of CB compared to the PHS samples for all level of education. There was an increase in the level of CB started from certi cate level of education until bachelor level of education, however, the level of CB showed a signi cant decrease at the level of masters and Ph.D. As Vujanić et al (2020) argue that this is because nurses with Bachelor of Nursing level of education are oriented towards organizational work, management, administrative work, and communication with other healthcare professionals. Therefore, nurses with a higher level of education have less time to interact directly with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Needlessness, Zhang et al (2021) found that there are differences in nurses' behavior according to where they work, and demographic factors have signi cant differences between different work environments. In applying CB, nurses give great priority to providing health care to meet the human needs and the environment in which they work (Vujanić et al, 2020). By considering demographic factors, nurses with 15 years of work experience, rated their CB signi cantly lower than 30 years of work experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main key that nurses can apply Caring's theory is at the level of knowledge and education of nurses. Nurses who have sufficient knowledge and high education will influence the application of caring behavior to patients (41). patients with acute or chronic diseases such as heart disease; it is very affordable and does not cause serious side effects.…”
Section: Complementary and Alternative Therapy Based On Phylosophycalmentioning
confidence: 99%